(untitled) (Revista Española de Fisiología, 1980)
Rat liver inner mitochondrial membranes have been subjected to the solubilizing action of the non-ionic detergent Triton X-100 under a variety of ionic strength and temperature conditions.Increasing ionic strength has little influence on the amount of solubilized membrane protein and lipid phosphorus.Calcium chloride actually increases the proportion of solubilized protein.This effect is preserved by 1 mM EDTA.Increasing temperatures tend to decrease the proportion of protein solubilized by the detergent.SDS-polyacrylamide gel electrophoresis fails to reveal any difference in polypeptide composition of the membrane fraction solubilized under the various conditions.However, differences are observed in the solubilization of individual cytochromes.The data are interpreted in terms of changes in membrane architecture induced by the various conditions of the incubation medium.